Not extinct after all: rediscovery of Commelina dielsii (Commelinaceae) after 140 years, and first record of this species in Uruguay - González, Andrés; Hassemer, Gustavo (Phytotaxa, 2020)
Commelina dielsii is a species notable for being, together with the southern Brazilian C. catharinensis, the only native Commelina from the Americas with yellow petals. The species was up until now only known from the type gathering, made in 1878 in Entre Ríos province, north-eastern Argentina. Because it had not been collected since then, the species was considered as likely extinct. We present here the rediscovery of this species after 140 years, as the species was recently found in western Uruguay, in pampean environment. This also corresponds to the first record of the species in Uruguay. We also present field photographs, a morphological description, a distribution map for the species and its conservation status assessment.